923 Accuracy of Assessment in Hand Trauma; Pre COVID-19 Face to Face Assessment Compared to Virtual Assessment During COVID-19 Lockdown. (4th May 2021) - Westley, S; Creasy, H; Mistry, R
Abstract: Introduction: The Queen Victoria Hospital (QVH) was designated a cancer and trauma hub during the COVID-19 pandemic. With this, a new virtual hand trauma clinic was set up. We assess accuracy of assessment within this virtual set-up with comparison to pre COVID-19 face-to-face assessment. Method: Two weeks of clinic sessions during and pre lockdown were analysed. Initial assessment was compared with the patient's operation note. Results: In the pre COVID-19 two-week period 129 face-to-face appointments were analysed. Of 99 patients that required surgery 77 (78%) had an accurate assessment. 6 were overestimated, 12 were underestimated. 189 patients were seen over two weeks during lockdown via telephone or video call. Accuracy of assessment increased with seniority of the clinician. Of 126 patients that required an operation 109 (87%) had an accurate assessment; all structures injured were correctly predicted. 12 were overestimated, 5 had their injury underestimated. Conclusions: The new virtual clinic allowed patients to be remotely assessed during lockdown, reducing footfall and unnecessary journeys. We found that virtual clinic assessments are accurate, and no patient underwent an unnecessary procedure. Using a telephone call plus photo gave similar accuracy as a video call. Virtual assessment was more accurate than face-to-face assessment.